The effect of muscle defect size on donor site hernia and bulge after transverse rectus abdominis flap - Yumin Kim; Ji-Young Kim; Hak Chang (Journal of Plastic Surgery and Hand Surgery)
Background: Muscle sparing-transverse rectus abdominis flap has been widely used for breast reconstruction and the abdominal hernia or bulging at the donor site is relatively common complication. Previous studies have emphasized the fascial defects and the defect of muscle has been neglected. This study aims to investigate the relationship between the size of the rectus abdominis muscle defect and its impact on hernia or bulge formation after muscle sparing-transverse rectus abdominis flap.